Removal of Organic Matter Contained in Slaughterhouse Wastewater Using a Combination of Anaerobic Digestion and Solar Photoelectro-Fenton Processes - Salazar-Gonzalez, R; Huilinir-Curio, C; Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier Ltd, 2016)
Here, the mineralization of organic matter present in slaughterhouse wastewater from a Chilean meat company was achieved by a combination of anaerobic digestion followed by the solar photoelectro-Fenton (SPEF) process. The first step was the biological treatment, during which 90% of COD removal was achieved, producing 90 mL of CH4. Further, the post-biological effluent showed lower color, odor, amount of solids and turbidity but higher conductivity due to an increase in the concentration of NH4+ and NO3-. This was followed by different electrochemical advanced oxidation processes (EAOPs): electro-oxidation (EO), electro-Fenton (EF) and SPEF. With SPEF, almost complete mineralization was achieved with a high efficiency. With SPEF, the fast mineralization rate is due to hydroxyl radicals (OH) that are generated in the bulk, on the anode surface, by solar radiation, and most importantly, by the direct photolysis of complexes formed between Fe3+ and some organic intermediates. The combination of both processes, biological digestion and SPEF, produces a totally clarified effluent, with a COD removal greater than the separate processes and better than the final effluent from industrial wastewater plants at comparable reaction times. © 2016 Elsevier Ltd. All rights reserved.